Divozilimab in neuromyelitis optica spectrum disorders: Evidence-based consensus of Russian committees of experts and clinical potential - V. S. Krasnov; Ya. V. Vlasov; E. Р. Evdoshenko; D. S. Korobko; V. М. Lebedev; I. G. Lukashevich; A. I. Nilov; E. S. Novikova; E. V. Popova; K. V. Sapozhnikov; A. А. Sokolova; N. А. Totolyan; et al. (Meditsinskiy sovet = Medical Council, 2026)
Neuromyelitis optica spectrum disorders (NMOSD) are a group of inflammatory diseases of the central nervous system. B-lymphocytes play leading role in their pathogenesis in most cases. СD20 surface antigen is one of the B-lymphocytes makers. There is extensive world experience with chimeric monoclonal anti-CD20 antibody rituximab off-label using for NMOSD exacerbations prevention. It has been included in published international and Russian algorithms for NMOSD treatment along with other approved medications. Divozilimab is recombinant humanized anti-CD20 monoclonal antibody with a modified glycosylation pattern of Fc-fragment which is approved in Russian Federation for the treatment of multiple sclerosis, systemic scleroderma and also for NMOSD (September 2025). The publication is intended to present the results of the Russian Expert Councils work in September 2025 and February 2026. According to the analysis of publications on anti-CD20 NMOSD therapy, the 6-month results of divozilimab study BCD-132-6/AQUARELLE (NCT05730699) and data of additional subanalysis experts agreed the profiles of NMOSD patients for divozilimab therapy, time to full therapeutic effect and monitoring plan during treatment with divozilimab. Experts supplemented the algorithm for initial prescription and switching of medications for prevention of NMOSD attacks in patients with AQP4-IgG aged 18 years and older, agreed on the algorithm for the administration of medications for prevention of NMOSD attack in patients without AQP4-IgG aged 18 years and older, determined positions of divozilimab in both algorithms. According to experts opinion divozilimab appears as promising treatment option in NMOSD. Analysis of divozilimab effectiveness and safety long-term results in BCD-132-6/AQUARELLE study and real-world practice will be important steps toward clarifying and potentially extending patient profiles.